2010
DOI: 10.1021/ac102523q
|View full text |Cite
|
Sign up to set email alerts
|

HILIC-UPLC-MS for Exploratory Urinary Metabolic Profiling in Toxicological Studies

Abstract: Hydrophilic interaction ultra performance liquid chromatography (HILIC-UPLC) permits the analysis of highly polar metabolites, providing complementary information to reversed-phase (RP) chromatography. HILIC-UPLC-TOF-MS was investigated for the global metabolic profiling of rat urine samples generated in an experimental hepatotoxicity study of galactosamine (galN) and the concomitant investigation of the protective effect of glycine. Within-run repeatability and stability over a large sample batch (>200 sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 49 publications
5
111
0
2
Order By: Relevance
“…Retention occurs through solute partitioning between a pseudoimmobilised water layer and the bulk mobile phase, as well as by adsorption and ionic interactions. There are important applications of the technique in biomedical and biological science, including in pharmaceutical analysis [1], metabolomic fingerprinting [2,3], anti-doping investigations [4,5] and clinical applications [6]. The mobile phases used in HILIC are typically hydro-organic mixtures of an aprotic solvent such as acetonitrile (>70%ACN, v/v) in the presence of a soluble buffer (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Retention occurs through solute partitioning between a pseudoimmobilised water layer and the bulk mobile phase, as well as by adsorption and ionic interactions. There are important applications of the technique in biomedical and biological science, including in pharmaceutical analysis [1], metabolomic fingerprinting [2,3], anti-doping investigations [4,5] and clinical applications [6]. The mobile phases used in HILIC are typically hydro-organic mixtures of an aprotic solvent such as acetonitrile (>70%ACN, v/v) in the presence of a soluble buffer (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The analyzed data was exported to Simca 14 (Umetrics, Umea, Sweden) for multivariate analysis. Data quality was evaluated in terms of reproducibility using an approach utilize in others works by Spagou et al, 2011. As a quality control estimate all the spectral data were mean centered, pareto scaled and analyzed with principal components analysis (PCA).…”
Section: Discussionmentioning
confidence: 99%
“…is is also because there has been no de nite and versatile inlet method that is able to simultaneously separate a wide variety of metabolites. In the case of LC/MS metabolomics, there are at least 5 groups of LC conditions, which include reverse phase analysis using octadecylsilyl (ODS) column for relatively hydrophobic metabolites, 45) normal phase analysis using columns for hydrophilic interaction chromatography (HILIC) of hydrophilic metabolites, [46][47][48] reverse phase analysis using pentafluorophenylpropyl stationary phase column for hydrophilic metabolites, 49) ion-paring methods using ODS column for anionic metabolites, 50) and lipidomics methods using ODS column for lipids. Recently, a comparison of the chromatographic performance of a traditional ODS column with various HILIC and mixed-mode columns showed that ODS and zwitterionic HILIC columns are the best combination for wide metabolite coverage.…”
Section: Bottleneck In the Metabolomics 2: Quantification Without Valmentioning
confidence: 99%